Porcine Gasdermin D Is a Substrate of Caspase-1 and an Executioner of Pyroptosis - Song, Yueyang; Song, Jiameng; Wang, Meng; Wang, Junwei; Ma, Bo; Zhang, Wenlong (Frontiers in Immunology, 2022)
Gasdermin (GSDM) family proteins were recently identified as the executioner of pyroptosis. The mechanism of pyroptosis mediated by gasdermin D (GSDMD) (a member of GSDM family)in humans and mice is well understood. In pyroptosis, mouse and human GSDMDs are cleaved by activated proinflammatory caspases (caspase-1, 4, 5, or 11) to produce anamino-terminal domain (GSDMD-NT) and a carboxyl-terminal domain (GSDMD-CT). The GSDMD-NT drives cell membrane rupture, which leads to the pyroptositic death of the cells. The expression of porcine GSDMD (pGSDMD) has recently been determined, but the activation and regulation mechanism of pGSDMD and its ability to mediate pyroptosis are largely unknown. In the present study, the activation of porcine caspase-1 (pcaspase-1) and cleavage of pGSDMD occurred in the duodenum and jejunum of a piglet challenged with enterotoxigenic Escherichia coliwere first determined. Then the capability of pcaspase-1 to cleave pGSDMD was determined in a cell-free system and in human embryonic kidney cells. The pGSDMD cleavage by pcaspase-1 occurred after the pGSDMD molecule’s 276Phenylalanine-Glutamine-Serine-Asparticacid279 motif. The pGSDMD-NT generated from the pGSDMD cleavage by pcaspase-1 showed the ability to drive cell membrane rupture in eukaryotic cells. When expressed in E. coli competent cells, pGSDMD-NT showed bactericidal activity. These results suggest that pGSDMD is a substate of pcaspase-1and an executioner of pyroptosis. Our work sheds light on pGSDMD’s activation mechanisms and functions.